Delayed-type hypersensitivity responses in mice infected with St. Louis encephalitis virus: kinetics of the response and effects of immunoregulatory agents. - Hudson, B W (1979)
Labeled monocyte infiltration techniques have been used to study delayed-type hypersensitivity responses in mice immunized with St. Louis encephalitis virus. A delayed 24- to 48-h inflammatory response occurred 6 to 7 days after immunization. This response can be potentiated by cyclophosphamide treatment, by BCG administration, or by splenectomy. Treatments known to selectivity inhibit T-cell function suppressed the response.